2007
DOI: 10.4319/lo.2007.52.4.1430
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation to a dynamic irradiance regime changes excessive irradiance sensitivity of Emiliania huxleyi and Thalassiosira weissflogii

Abstract: Effects of fluctuating irradiance regimes on excessive photosynthetically active radiation (PAR) and ultraviolet (UV) radiation sensitivity were assessed for Emiliania huxleyi (Lohman) and Thalassiosira weissflogii (Grunow) Fryxell and Hasle. Cultures acclimated to low irradiance were subjected to two irradiance regimes of equal daily dose: dynamic irradiance simulating vertical mixing within the water column and constant irradiance. For each regime two irradiance levels were studied. Growth was monitored for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 28 publications
(44 reference statements)
3
46
2
Order By: Relevance
“…This suggests that during the mixing process, phytoplankton at deep mixed layer stations were exposed to a range of irradiance intensities and acclimating to lower levels of irradiance. Laboratory experiments have shown that diatoms and haptophytes exposed to fluctuation in irradiance are acclimating to lower irradiances than cells grown under constant irradiance (van de Poll et al, 2007(van de Poll et al, , 2009). This could explain the lower ratios of DDþDT to TChl-a at these stations.…”
Section: Influence Of Light In the Shallow And Deep Mixed Layermentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that during the mixing process, phytoplankton at deep mixed layer stations were exposed to a range of irradiance intensities and acclimating to lower levels of irradiance. Laboratory experiments have shown that diatoms and haptophytes exposed to fluctuation in irradiance are acclimating to lower irradiances than cells grown under constant irradiance (van de Poll et al, 2007(van de Poll et al, , 2009). This could explain the lower ratios of DDþDT to TChl-a at these stations.…”
Section: Influence Of Light In the Shallow And Deep Mixed Layermentioning
confidence: 99%
“…In contrast, under low iron high light conditions, photoinhibition or photodamage may occur as iron limitation decreases the synthesis of cytochrome b 6 f complexes, an enzyme required in the activation of photoprotective mechanisms (Strzepek and Harrison, 2004;van de Poll et al, 2009). Thus, iron-limited cells are less efficient at coping with an environment with rapid irradiance fluctuations than iron-replete cells (Strzepek and Harrison, 2004;van de Poll et al, 2009;Alderkamp et al, 2012). In addition, under iron-Si(OH) 4 colimitation conditions, growth of non-silicious, iron-efficient phytoplankton species such as eukaryotic picoplankton and cyanobacteria often dominate over larger cells (Hutchins et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Pelagomonas calceo lata were transferred to 500 ml glass Erlenmeyer flasks and incubated in triplicate at 16, 20 and 24°C. Experiments were carried out in a temperature-controlled U-shaped lamp setup as described by Van de Poll et al (2007). The temperature in the setup was maintained at 16, 20 and 24°C by a thermostat (RK 8 KS, edition 2000, Lauda Dr. R. Wobser & Co.) and deviated by less than ± 0.5°C.…”
Section: Experimental Designmentioning
confidence: 99%
“…Fluctuation of solar radiation on cloudy days led to higher primary production in the presence of UVA (315-400 nm) as compared with the presence of UVA on sunny days . Algal acclimation to fluctuating irradiance can lead to differences in growth rates and cellular pigment content compared with the cells acclimated to constant irradiance (Van de Poll et al, 2007. On the other hand, the mixing rate in the UML is strongly controlled by wind (Denman and Gargett, 1983;MacIntyre, 1993), which may increase due to global warming (Toggweiler and Russell, 2008).…”
mentioning
confidence: 99%